Characteristics of newborns with difficulty breastfeeding in a University Hospital: An epidemiological study (Research, Society and Development, 2022)
Objective: To identify epidemiological characteristics such as gestational age, type of delivery and the sex of neonates with breastfeeding difficulties in a teaching hospital in western Paraná. Methodology: Descriptive epidemiological study from a primary source, carried out at the maternal and child care unit of the Hospital Universitário do Oeste do Paraná (HUOP) between March and September 2021. Neonates up to 24 hours old who had reported breastfeeding difficulties were selected for the study. by the mother and with a score greater than seven on the LATCH scale. Results: The study sample consisted of seventy newborns for the study, thirty-seven males born by vaginal delivery (52.9%), thirty-three females born by cesarean section (47.1%). Gestational age ranged between thirty-seven and forty-one weeks of gestation, with the most predominant being thirty-nine weeks (38.6%), followed by thirty-eight (24.3%) and forty weeks (17.1% ). Conclusion: The present study demonstrated that the characteristics of neonates with breastfeeding difficulties at a teaching hospital in western Paraná, which are mostly male neonates, born by vaginal delivery and with a gestational age of 39 weeks.